PENDESAINAN MODEL MANAJEMEN EVENT KOMUNITAS: PERENCANAAN, PELAKSANAAN, EVALUASI, DAN KEBERLANJUTAN - Jopinus Saragih; Adrian K. Tarigan; Oktora Jubileus Sinambela (Yayasan Nusantara Hasana Berdikari, 2024)
This Community Engagement (PkM) activity aims to design and implement a practical and replicable community event management model, covering the planning, execution, evaluation, and sustainability phases. Common challenges faced by partners include unclear role assignments, schedules that frequently change without proper oversight, poorly documented budget and vendor management, and non-standardized activity reporting. Interventions are carried out through community needs mapping, the development of SOPs and working documents (TOR, WBS, timeline, RACI, budget, risk management, communication plan), committee training, implementation support for pilot events, as well as indicator-based (KPI) evaluation and participant feedback. Outputs include a pocket guide on event management models, standard document templates, event evaluation reports, and plans for program sustainability and community agendas.